Prevalência de incontinência urinária de esforço em praticantes de CrossFit - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá, 2023)
Stress urinary incontinence in female CrossFit practitioners is a common complaint. Objective: to investigate whether there is a prevalence of stress urinary incontinence (SUI) in women who practice CrossFit® in the city of Macapá. Methodology: the study was descriptive, cross-sectional, with a quantitative approach. The data were generated through a form produced in Google Forms for the demographic profile and the Consultation on Incontinence Questionnaire – Short Form (ICIQ-UI-SF) was used, which allowed to assess the perception of the participants about the probability of loss of urine. Subjects: 78 women aged between 20 and 50 years participated in the research. Results: Demographic data revealed that the majority of the participants, 43.6%, were graduates. They present regular intimate health and are nulliparous. Of these women, 25.6% never had involuntary loss, 41% lost urine, 4.1% lost it once, 11.5% lost it twice, and only 7.7% were involuntarily losing urine daily. Finally, the loss of urine, for the majority 40.3%, does not interfere with anything in daily life. As for the frequency of urinary loss, the data also showed that the majority 40.8% lose it only once or less a week, 34.2% never, 19.7% twice or three times a week, 2.6% several times a day, 1.3% once a day, and 1.3% all the time. With regard to the voice perception of urine that was lost as: 49.4% a small amount, 31.2% none and 19.5% a moderate amount, a large amount did not show a percentage. When it comes to the moment when they lose it, it is evident that 46.8% have urine loss when they practice physical activities, 45.5% when they cough or sneeze. Conclusion: The hypothesis raised was that, as it is an impact modality, it could be an aggravating factor or cause of UI. However, the findings showed that, although the women did not attest to a severe condition of involuntary urine loss, the fact that most lose it during physical activities and when sneezing or coughing corroborates the literature in the area, which in the participants of the study, women who practice CrossFit®, there is a prevalence of stress UI. Thus, the data lead to the understanding that the practice of CrossFit would not, in principle, be a determinant of the cause of UI.
Keywords: Incontinência Urinária; Diafragma da Pelve; Exercício Físico; CNPQ::CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL; ODS 3 – Saúde e bem-estar